Holocene environmental history in high‐Arctic North Greenland revealed by a combined biomarker and macrofossil approach. (28th January 2019) - Kusch, Stephanie; Bennike, Ole; Wagner, Bernd; Lenz, Matthias; Steffen, Ilona; Rethemeyer, Janet
Abstract : In this study, we use a combined biomarker and macrofossil approach to reconstruct the Holocene climate history recorded in Trifna Sø, Skallingen area, eastern North Greenland. Chronological information is derived from comparison of lithological, biogeochemical and macrofossil characteristics with a well‐dated record from nearby Lille Sneha Sø. Following local deglaciation around c . 8 cal. ka BP, the local peak warmth occurred between c . 7.4 and 6.2 cal. ka BP as indicated by maximum macrofossil abundances of warmth‐demanding plants ( Salix arctica and Dryas integrifolia ) and invertebrates ( Daphnia pulex and Chironomidae). Warm conditions were dominated by terrestrial organic matter (OM) sedimentation as implied by the alkane‐based Paq ratio, but increased aquatic productivity is indicated when temperature was highest around 6.5 cal. ka BP. The n ‐C29 / n ‐C31 alkane ratio shows that vegetation in the catchment was dominated by shrubs after deglaciation, but shifted towards relatively more grassy/herbaceous vegetation during peak warmth. After 5.4 cal. ka BP, the disappearance of warmth‐demanding plant and invertebrate macrofossils indicates cooling in the Skallingen area. This cooling was characterized by a significant shift towards dominance of aquatic OM sedimentation in Trifna Sø as implied by high Paq ratios. Cooling was also associated with a shift in vegetation type from dwarf‐shrub heaths towards relatively more herbaceous vegetation in the catchment, stronger erosion and more oligotrophic conditions in the lake. Our data show that mean air temperatures inferred using branched glycerol dialkyl glycerol tetraethers (brGDGTs) do not seem to accurately reflect the local climatic history. Irrespective of calibration, methylation of branched tetraethers (MBT) palaeothermometry cannot be reconciled with the macrofossil evidence and seems to be biased by either changing brGDGT sources ( in situ vs. soil‐derived) or changing species assemblages and/or an unknown physiological response to changing environmental conditions at high latitude.